The strategic path and policy consideration of trade of cultural products among WTO member countries: taking the circulation of cultural products derived from Dunhuang murals as an example - Md Yusoff, Irwan Syah; Fei, Liu; Alli, Hassan (Yijun Institute of International Law, 2024)
Transnational tourism has increased cultural product trade. Trade of cultural heritage like China's Dunhuang Murals illustrates this in the study. The Dunhuang Murals, a famous Chinese cultural depiction, have inspired many cultural tourism offerings. These products, along with murals, are popular with foreign tourists, requiring a WTO trade strategy. This study examines Dunhuang Murals’ cultural tourism product trade strategy and policy. Murals are not the focus, but the commercialization of products inspired by them. China's role in the WTO, Dunhuang Murals supply chain optimization, tourist preferences, and WTO cultural product trade implications are examined in the study. This study uses mixed methods in which surveys and trade analysis provide quantitative data, while stakeholder interviews and focus groups provide qualitative data. International trade agreements and cultural heritage protection laws are contextualized by extensive document analysis. A sample includes reliable 384 tourist responses are analyzed to identify key characteristics and spending habits. For qualitative research analysis, we conducted 12 interviews for more clarification of context. The results show that a complex business ecosystem is revealed by Dunhuang Murals product trade analysis. The findings emphasize sustainable tourism, authenticity, quality, and fair trade. This study found that addressing supply chain issues, ensuring product authenticity and quality, and implementing fair trade policies optimizes cultural product trade. Policymakers, stakeholders, and cultural heritage agencies can use the findings to promote sustainable tourism and trade while preserving the Dunhuang Murals.